Analysis of Financial Performance Ratio of Medan City Government 2020 – 2023 - Pitaloka, Allika Ayu Diah; Syahputri, Cindy; Anggreani, Nabilla Puteri; Indriani, Sela; Chrisna, Heriyati (Jurnal Riset Ilmu Pendidikan, 2024)
Financial performance measurement is very necessary to assess regional government accountability in financial management. Accountability is not only about the ability to demonstrate the use of public money, but also includes the ability to prove that such use was carried out efficiently, effectively and economically. Currently, the Medan City Government is facing problems related to the percentage of PAD achieved from 2020 to 2023. This research aims to analyze the financial performance of the City of Medan using Regional Financial Independence Ratio Analysis, PAD Effectiveness Ratio, PAD Efficiency Ratio, Degree of Decentralization Ratio, Growth Ratio, and Conformity Ratio in the 2020-2023 period. The method used is quantitative descriptive, namely calculating financial data obtained to solve problems by analyzing various ratios. The findings of this research show that the financial performance of the Medan City Government is quite good in terms of independence, in the "delegative" category, but the effectiveness ratio and efficiency ratio aspects require more attention because the average ratio results show the less effective and less efficient categories. In terms of the degree of decentralization, the results are in the "medium" category, where PAD makes a fairly good contribution to regional income in the Medan City Government. The crowd ratio shows that the percentage of APBD used for operational expenditure is higher, namely 76.23% compared to capital expenditure which is only 23.77%. Regional income and expenditure in the Medan City Government shows a decrease and increase every year.